Stress-associated factors among nursing students in higher education in east Malaysia - Caroline Satu; Baidi Baddiri; Rohani Mamat; Mazlinda Musa; Clarice Duasin; Chung, Su Chin; Muhammad Idris Bullare @ Bahari; Siti Fatimah Saat (Program Keperawatan, Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Surakarta, 2024)
Psychological distress among students leads to less productivity, reduced quality of life, and learning difficulties and may negatively affect patient care. Objective: The main aim of this study is to identify stress factors among UMS students. A cross-sectional descriptive, universal sampling of 152 student nurses was included in this study. Respondents were given a self-answered structured questionnaire conclusive of socio-demographic data, the Perceived Stress Scale (PSS-10), and factors associated with stress. A descriptive analysis was used to analyze the data. Results & Findings, out of 152 students, the majority have moderate stress (83.6 %), about 12.5 % have low-stress levels, and only 3.9 % of respondents have high stress levels. The results show that students experienced or reported significantly higher academic factors (24.9 %), followed by interpersonal factors (24.6 %) Conclusion: According to study findings, stress is most prevalent among nursing students and is attributed to academic and interpersonal causes. It is advised to use proactive learning strategies, peer and staff mentoring and modeling, professional networks and social support, psychological support, and faculty role and behavior.